Evaluation of the accomplishment of the social responsibility in the cattle genetic enterprise "Camilo Cienfuegos" - Osvell García Valido; Alvaro Celestino Alonso Vázquez; Osvaldo Dominguez Junco (Cooperativismo y Desarrollo, 2019)
Amid the growing prevailing globalization, an important part of the managerial union in many countries, it has recognized the more and more excellent paper of their companies in the economic, environmental and social transformation of the geographical areas where they act, because of the impact that you/they generate and they reach. These behaviors or ways of assuming aware commitments of contributing with the sustainable development and the improvement of the quality of the workers' life, their families, the community and the society in general, on the base of efficient and effective economic processes, it contains the acting of the Managerial Social Responsibility. The present work has as objective to evaluate the practices in Managerial Social Responsibility of the Genetic Cattle Company Camilo Cienfuegos. For the realization of this, the following methods were used: the historical-logical, systemic and statistical with their different ones technical. As a result an evaluation is obtained on the part of the surrounding population to the entity, as well as of its workers, technicians and specialists of like they perceive the Managerial Social Responsibility carried out by the study entity, starting from excellent aspects related with five fundamental environments: organizational environment, economic and financial environment, environmental environment, environment of programs and projects and innovative and technological environment, which allowed to classify as positive the acting of the Managerial Social Responsibility in this entity.